ON THE NORMALITY OF SOME CAYLEY DIGRAPHS WITH VALENCY 2 - Alaeiyan, Mehdi (IndoMS, 2011)
We call a Cayley digraph ô€€€=Cay(G; S) normal for G if R(G), the rightregular representation of G, is a normal subgroup of the full automorphism groupAut(ô€€€) of ô€€€. In this paper we determine the normality of Cayley digraphs of valency2 on the groups of order pq and also on non-abelian nite groups G such that everyproper subgroup of G is abelian.DOI :Â http://dx.doi.org/10.22342/jims.17.2.3.67-72